THE SUFISM DEFENSE OF IBN HAJAR AL-HAYTAMI: FATWAS ABOUT SUFISM IN HIS WORK AL-FATAWA AL-HADITHIYYAH - Mehmet Saki ÇAKIR (Fırat University, 2020)
Ibn Hajar al-Haytami (d. 974/1567), was a famous muhaddith and faqeeh, has the right to sufism and has the authority (ijazah) of a sufi order. This 'aalim (scholar), who lived in Egypt in the 16th century, gave answers to the sufism issues that were asked to him from a faqeeh perspective. These fatwas in the last chapter of Al-Fatawa al-Hadithiyyah are important in terms of reflecting his view of sufism. Because he touched even the most basic issues such as the definition of Sufism. Another issue he mentioned is the relationship between Sharia and tariqa. According to him, although these two areas are different, they are not opposed to each other and intersect at some point. al-Haytami, who accepts the truth of inspiration (ilham), says that the Islamic jurist (faqeeh) does not accept it as evidence. al-Haytami, who defended Ibn ‘Arabi and Ibn al-Farid, tried to establish a legitimacy ground for the words of ecstasy (shathiyya) of Al-Hallaj and Bayazid. In this defense, he explained the words of the Sufis